Defending Alice : a novel of love and race in the roaring twenties - Stratton, Richard (Richard H.) (HarperVia, an imprint of HarperCollinsPublishers, 2022)
In a novel based on a real-life case, 1920s New York society is set ablaze when Alice Jones, a working-class woman with at least one black parent, marries Leonard "Kip" Rhinelander, the son of a wealthy, prominent family, who makes international headlines after he sues for annulment, accusing her of hiding her "Negro blood."